An evaluation of the hypodermic needle threat against body armour - Watson, Celia H.; Horsfall, Ian; Luk, Edwina (Cranfield University, 2004)
Previous work has addressed protection against stab attacks [1, 2], and slash attacks [3, 4] this has resulted in body armour that is suitable for protecting the torso against knives. Whilst this armour combats the primary lethal injuries to the torso it does not protect against minor injuries to the limbs and hands from items such as hypodermic needles and other sharp weapons. To reduce injuries to the hands from sharp weapons and needles there is a need for an effective protective glove and also a protective sleeve for the arms. This paper investigates the threats posed by hypodermic needles and examines the effectiveness of various possible needle proof systems. In order to determine the contact loads from needles that might be encountered whilst conducting body searches, male and female volunteers used an instrumented impact system to measure the average impact forces of human hand against a fixed object. The compressive loads a hand imparts as it grips an object to pick it up were also measured. A range of sizes of hypodermic needles were used to measure the puncture resistance of several lightweight armour materials and the buckling loads of the needles were also determined. This study showed that the buckling loads for hypodermic needles were much lower than typical loads measured in the human tests for accidental contact or gripping. Although a hypodermic needle is able to puncture skin easily, when puncturing armour materials the needles tended to buckle.